EXPERIMENTAL JUSTIFICATION OF IDENTITY FEATURE CHOICE OF PALM OILS - Zh. V. Kadolich; S. V. Zotov; V. A. Goldade; E. A. Tsvetkova; K. V. Ovchinnikov; I. Yu. Ukhartseva (Приборы и методы измерений)
The method of thermally activated current spectroscopy was used for identification of two popular types of palm oils. The spectrum of thermally stimulated currents represents sufficiently intensive (up to 10-11 А) current peaks conditioned by differences in fatty-acid composition of oils. Introduction of representation on unstable associates, in which coordination bonds connect molecules of fat acid’s glycerides, allow interpret the experimental data about the current response at oil specimens heating. The current’s peaks location in a certain temperature range of TSC spectrum can be considered as an identify feature of investigated vegetable oils.